Preparation of modified rare earth lanthanum oxide/polypropylene nonwoven fabric by meltblown method. Issue 1 (1st February 2022) - Sun, Yunhan; Wang, Xiaoning; Jia, Qingxiu; Yang, Jian
Abstract: Lanthanum oxide was organically modified with dopamine and blended with polypropylene, and then lanthanum oxide (La2 O3 )/polypropylene (PP) nonwovens were prepared by melt blown method. The nonwovens were characterized by FTIR, SEM, TG, mechanical properties and X-ray shielding. The experimental results show that the addition of modified La2 O3 makes the fiber arrangement of PP nonwovens more densely arranged and improves the thermal stability of PP nonwovens. The higher the amount of La2 O3, the better the X-ray shielding performance of composite nonwovens.